Studi Analisis Terhadap Peran Guru Mengoptimalisasi Manajemen Pembelajaran Agama Kristen - Melyarmes Hodner Kuanine; Gusti Yohanis Sette (Institut Agama Kristen Negeri Manado, 2022)
The purpose of this study is to see the extent to which the teacher's role in optimizing and improving the management of Christian religious learning. To obtain research data, the author uses a descriptive qualitative research approach by means of a literature review. The results of this study indicate that, firstly, the teacher's role in optimizing the management of Christian religious learning is very important, so the teacher as the main actor in this case needs to carry out his responsibilities and fulfill his calling and obligations to students. Second, the success of PAK teachers in learning can be seen from their competence, implementing management values ​​well. The inability of teachers to optimize management values ​​in PAK learning is the cause of student outputs who are unable to develop an educational mission. Therefore, improvements to the management of Christian religious learning must be carried out for the realization of effective learning. Third, learning management must be implemented by considering various developmental conditions that will later be realized in the learning process that is actualized by students. So in the context of learning management, it is a must for PAK teachers to plan learning management functions regularly, including techniques or methods to equip students to consistently interpret learning.